Application of the Pbl Learning Model Assisted by Video Media to Improve Student Learning Outcomes at Sman 1 Haharu - Tonda, Mutiara Rambu; Makaborang, Yohana; Enda, Riwa Rambu Hada (FKIP - Universitas Riau, 2024)
The problem found based on the results of interviews with science teachers at SMAN 1 Haharu, is that the learning model used so far is discovery learning. This learning model is less efficient to apply and the learning process does not use learning media such as power point and other video media. The aim of this research is to describe the increase in learning outcomes after implementing the problem based learning model assisted by video media to improve the learning outcomes of class XI students at SMAN 1 Haharu. This type of research is a type of classroom action research with a descriptive quantitative approach. Research is carried out in classes using cycles. The research stages are: planning, implementation, observation and reflection. The subjects of this research were students of class XI Science at SMAN 1 Haharu. The data collection techniques and instruments used were tests and affective assessment sheets. The data analysis technique is calculating the average score, calculating student learning completeness in cognitive assessment and calculating student learning completeness in affective assessment. The research results can be seen from the comparison of the average values for each cycle in the pre-cycle 65.96, cycle I 73.46, and cycle II 78.1. These results can be said to have increased. It can be concluded that the application of the problem based learning model assisted by video media can improve the learning outcomes of class XI Science students at SMAN 1 Haharu.